What role does stream restoration play in nutrient management?. Issue 6 (19th March 2017) - Lammers, Roderick W.; Bledsoe, Brian P.
ABSTRACT: Nutrient pollution is a pervasive water quality problem. Stream restoration has been proposed as a novel approach to reduce loading and increase nutrient processing within streams. We summarize evidence from the literature on the efficacy of stream restoration for reducing nutrient loading and increasing nutrient removal in stream ecosystems. We also analyze published data on streambank phosphorus concentrations and riparian and stream denitrification rates to improve understanding of the potential benefits of stream restoration for phosphorus retention and nitrogen removal. Finally, we discuss the role of stream restoration in nutrient management and provide recommendations for practice and future research.